Model based characterisation of delamination by means of thermographic inspection. (March 2020) - Ratsakou, Almpion; Reboud, Christophe; Skarlatos, Anastassios; Lesselier, Dominique
Abstract: The objective of the work presented in this paper is to propose a fast and accurate approach for the characterisation of the delamination in single-layer metallic planar pieces using infrared thermography. This approach is based on a combination of pre-processing techniques and inversion. The inversion has been done in a reduced parameter space since the preprocessing phase gives us information about the location and the shape of the flaws in the transverse plane. The estimation of the flaws' parameters has been carried out by an iterative data fitting method involving a fast semi-analytical three-dimensional model. The robustness of the proposed approach is numerically assessed in presence of synthetic noisy data sets in different configurations.